Pembinaan Sosial-Keagamaan Lanjut Usia Dalam Membangun Konstruk Kesalehan Sosial - Sakirman Sakirman (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
This paper is the essence of the research on elderly socio-religious development in developing the construct of social piety in the Elderly Social Institution (PSLU) Bhakti Yuswa Lampung aims to find out the superior programs in Islamic religious formation to the elderly followed by why Islamic education is directed towards the elderly are in need and how the influence of the implementation of Islamic religious guidance on the elderly. Data analysis in this study used descriptive qualitative method with inductive thinking method. The results of this study indicate that Islamic religious formation is a process of spiritual rehabilitation. It is considered necessary to help the psychological condition of the elderly who experience spiritual disorders that can be overcome by carrying out activities that improve aspects of spirituality through excellent programs such as recitation, prayer building and fasting. The practice of Islamic religious activities can be done well by the elderly as evidenced by the description of the results of Islamic religious formation can improve aspects of spirituality as measured by the construct of social piety.